Effect of Green Human Resource Management on Corporate Environmental Performance: The Mediating Role of Green Innovation and Organizational Citizenship Behavior in Chinese Telecom Enterprises - Haiyun, Chen; Wongvanichtawee, Chalermkiat; Submahachok, Pattsornkun (Journal of Multidisciplinary in Humanities and Social Sciences, 2026)
This article aimed to study: 1) to explore the effects of green human resource management (GHRM), green innovation (GI) and organizational citizenship behaviour (OCB) on corporate environmental performance (CEP) in Chinese Telecommunication Enterprises. 2) to explore the effects of green human resource management (GHRM) through green innovation (GI) and organizational citizenship behaviour (OCB) that impact the corporate environmental performance (CEP) in Chinese Telecommunication Enterprises. A mixed-methods research approach was employed, integrating quantitative survey analysis with qualitative semi-structured interviews. In the quantitative phase, 369 valid responses were collected from employees across multiple Chinese telecommunication companies using structured questionnaires designed to measure green human resource management, green innovation, organizational citizenship behavior, and corporate environmental performance. The qualitative phase involved in-depth interviews with managers and employees, providing nuanced insights into the mechanisms by which green human resource management practices and green initiatives are implemented and experienced within organizations. The findings indicated that green human resource management, green innovation, and organizational citizenship behavior all exert significant positive effects on corporate environmental performance, with green innovation demonstrating the strongest direct influence, emphasizing its strategic role in driving environmental improvements. Organizational citizenship behavior also positively contributed to corporate environmental performance and further enhanced it indirectly by promoting green innovation. Green human resource management’s effect on corporate environmental performance was largely mediated through organizational citizenship behavior and green innovation, highlighting the systemic importance of cultivating employee engagement and innovation in green practices. Qualitative insights corroborated these results, revealing that effective green human resource management practices, including recruitment, training, and performance appraisal aligned with sustainability objectives, fostered a culture of environmental responsibility and enabled employees to actively participate in green innovation initiatives.